2010
DOI: 10.1007/s10528-010-9369-5
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Polymorphisms in Cassava Landraces from the Cerrado Biome, Mato Grosso do Sul, Brazil

Abstract: Using nine microsatellite loci, we investigated genetic structure and diversity in 83 Brazilian cassava accessions, including several landraces, in the Cerrado biome in Mato Grosso do Sul, Brazil. All nine loci were polymorphic, averaging 6.00 alleles per locus. Treating each of seven municipalities as a cassava group or population, they averaged 3.5 alleles per locus, with 97% polymorphic loci, high values for observed heterozygosity (0.32) and gene diversity (0.56). Total genetic variability was high (0.668)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
24
2
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 39 publications
10
24
2
5
Order By: Relevance
“…Among the phenotypic descriptors, the ones with agronomic importance are most influenced by the environment; however, they help to identify adapted accessions with productive potential (VIEIRA et al, 2013). Molecular markers are also frequently used in the estimation of genetic divergence in cassava (ASARE et al, 2011;FERREIRA et al, 2008;SIQUEIRA et al, 2010), since they are not affected by the environment and are efficient in the detection of a large number of differences among accessions (KRISHNAMURTHY et al, 2013). However, they have the disadvantage of accessing all the genome and not only the regions expressing traits of agronomic importance (VIEIRA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the phenotypic descriptors, the ones with agronomic importance are most influenced by the environment; however, they help to identify adapted accessions with productive potential (VIEIRA et al, 2013). Molecular markers are also frequently used in the estimation of genetic divergence in cassava (ASARE et al, 2011;FERREIRA et al, 2008;SIQUEIRA et al, 2010), since they are not affected by the environment and are efficient in the detection of a large number of differences among accessions (KRISHNAMURTHY et al, 2013). However, they have the disadvantage of accessing all the genome and not only the regions expressing traits of agronomic importance (VIEIRA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellites, or SSR (simple sequence repeats) molecular markers, are co-dominant and highly polymorphic markers (SIQUEIRA et al, 2010) with a high abundance in plants (MBA et al, 2001); they are used in studies of genetic divergence.…”
Section: Introductionmentioning
confidence: 99%
“…The Manihot genus (ALBUQUERQUE, 1969;HILLOCKS et al, 2002) may have originated and diversifi ed in Brazil where there is great genetic variety, mainly of local diversity, that is restricted to a few agriculturists. These varieties are known as landraces (SIQUEIRA et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This study also showed that there is a clear regionalization in the assignment of popular names for D. alata local varieties, according to their morphology, uses or origin. The role of farmers in maintaining the local agro-biodiversity, whether in home gardens or fields, is important for the maintenance of the genetic diversity of yams and other crops over generations (Chair et al, 2010;Siqueira et al, 2010;Bressan et al, 2011;Veasey et al, 2012). However, for these varieties to be maintained at an on farm conservation basis, agroecological conservation policy goals must be considered, as well as more studies emphasising the importance of yams in rural areas.…”
Section: Origin Of Dioscorea Alata Local Varieties and Their Usesmentioning
confidence: 99%